Appraisal of management and biosecurity practices on pig farms in Makurdi, Benue State, North Central Nigeria - Leo Daniel Ojabo; Moses Ukwu Enya (African Journal of Pig Farming, 2021)
The role of biosecurity at farm level is to reduce the risk of introduction of diseases in pig farms and prevent the disease transmission between animals on farms. It is an important management practice that impacts the profitability of pig production ventures. A survey was conducted to assess the biosecurity practices in 50 farms in Makurdi, Benue State, Nigeria, using a structured questionnaire and assessments through direct observations. Descriptive statistics such as frequencies, percentages and tables were used to analyse and present data generated. The results revealed that majority of the farms were semi-intensive (54%), small scale producers keeping between 1 and 50 pigs formed 96% of surveyed farms and essentially raising indigenous and crossbreed (72%). Only 12% of the farms were fenced and had gates closed to control unwanted visitors and stray animals. Most of the farms (76%) had no footbaths indicating that the risk of disease introduction was high in such farms. The use of protective clothings and foot wears by employees was only observed on 24% of the farms. Isolation of sick animal was practiced by 38% of respondents while 24% of respondents quarantined new animals to the farm. The use of disinfectants to clean the barns was practiced on 18% of the farms. Overall, there was a low level of farm biosecurity in the study area. Extension services to create awareness on the importance of biosecurity would help limit infections and boost pig production and profitability